Pijat Refleksi dan Penurunan Intensitas Nyeri pada Pasien Post Operasi Sectio Caesarea - Anita, Anita; Agustanti, Dwi; Purwati, Purwati (Jurnal Kesehatan, 2022)
Post Sectio Caesarea patients experience pain so they need postoperative adaptation. The pain felt by Sectio Cesarean patients comes from wounds in the abdomen. The pain usually occurs 10 to 36 hours after surgery and decreases on the third day. The purpose of this study was to determine the effect of reflexology on labor pain after a cesarean section. The research was conducted from August to October 2021, at Bhayangkara Hospital Bandar Lampung and RSIA AMC. Quasi-experimental research design with Wilcoxon signed rank. The research sample will be conducted on some 64 respondents (32 intervention respondents and 32 control respondents). Inclusion criteria for post-SC mothers, age 20-50 years, spinal anesthesia, intervention time 10 hours after post-SC, and mothers who are willing to receive reflexology. The results of the study the average score in the post-intervention foot reflexology group were 6.19 with a standard deviation of 644, the lowest pain scale was 4 and the highest pain scale was 7. The average score in the post-control group was 6.13 with a standard deviation of 535, the scale the lowest pain was 5 and the highest pain scale was 7. The results of the statistical analysis obtained showed that the p-value<0.05, and it was concluded that there was an effect of foot reflexology on reducing pain intensity in postoperative Sectio Caesarea patients. Learning recommendations add to the literature review related to foot reflexology and include in nursing services at health care institutions and further research on complementary therapies for post-op pain or palliative care.